Flashbacks in Film Noir - Gilles Menegaldo (Sillages Critiques)
Through the analysis of a body of films belonging to the “noir” genre, this article aims at specifying the various modes and functions of the flashback, a device which is often associated with the genre. This device is first part of the investigative structure and it helps feed the plot by allowing the reconstitution of an enigmatic past which may still bear upon the present. The flashback is also clearly associated with a subjective vision and it partakes of the confessional nature of the narrative as it is told by means of a voice over. The study of several opening scenes reveals the wealth and diversity of the strategies used to stage the flashback. Stanley Kubrick uses this device in a more innovative way. He subverts its functions and endows it with a more objective status, cut from the inner life of the characters.